Microfinance factors and religiosity influencing business performance of micro and small entrepreneurs (MSE) among TEKUN borrowers - Nadzreen Syakilah, Ahmad Nazri (2018)
The study aims to examine the relationship between microfinance factors (credit access, training, social capital) and religiosity on the business performance of micro and small entrepreneurs among TEKUN borrowers. Literature was reviewed in entrepreneurship, management, and other related fields to provide better understanding regarding past, present, and future needs in study area. Entrepreneurship has been identified as the vital tool for promoting economic and social growth for the nation. Entrepreneurship at the micro and small level helps to generate income at the household and national level. The micro finance institutions have been identified as the source of providing credit access and other tools in assisting entrepreneurs. Aside frotr1 that, religiosity is another aspect which influenced the development of entrepreneurship. The in-depth review of literature has led to the establishment of a theoretical framework to examine the relationship of microfinancc factors and religiosity with business performance. A questionnaire survey was designed and distributed towards the 320 entrepreneurs whom are borrowing from Tekun Nasional in Kedah. The study employed cluster sampling method and the result were analyzed using statistical analysis SPSS version 22. The surveys were distributed physically, and 102 responses were received. The findings of this study indicate that there is the relationship between credit access, training, social capital, and religiosity towards business performance. Credit access (r = 0.604) and religiosity (r = 0.637) have large correlation coefficient while training (r = 0.431) and social capital (r = 0.332) have medium correlation coefficient. Lastly, the discussion and explanation on limitation, theoretical and practical implications, limitations, direction for future research, and conclusions were included.